Revolutionizing Success: Unleashing the Power of Sustainability Balanced Scorecard for Optimal Performance in Transportation Services - Raisuli, Raga Bumi; Amrina, Uly (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
This study aimed to understand and analyze the performance measurement system within transportation service companies, focusing on the Sustainability Balanced Scorecard approach. Specifically, it outlined a process for developing a performance measurement strategy for PT Maju Logistik Transportindo, utilizing the Sustainability Balanced Scorecard (SBSC) and Analytical Hierarchy Process (AHP) methodologies. The research revealed prevalent issues often overlooked in transportation service companies during their internal assessments. Previously, PT Maju Logistik Transportindo's performance assessment primarily centered on financial aspects, neglecting a comprehensive evaluation. The Sustainability BSC method employed at the company expanded the evaluation to encompass four balanced scorecard perspectives—financial, customer, internal business, growth and learning—incorporating additional environmental and social viewpoints. This quantitative descriptive research employed survey methods, utilizing interviews and questionnaires for primary data collection. The process involved developing indicators grouped into the five perspectives of the Sustainability Balanced Scorecard to design performance measurements. The Analysis Hierarchy Process (AHP) was used to assign weights and priorities to each perspective. The result of measuring the performance of PT Maju Logistik Transportindo using BSC Sustainability is 91% which means it is very healthy if based on performance criteria.